Sustainable Linked Loans And The Blue Economy - Wanta, Derry; Mardianti , Ismi; Noviantoro , Rinto (Universitas Dehasen Bengkulu, 2025)
A Sustainable Linked Loan (SLL) is a loan that encourages the borrower to achieve ambitious sustainability performance targets. It specifically sets the link between sustainability goals and sustainability performance targets, measures the level of sustainability improvement, and ensures transparency through post-loan reporting. This research aims to see how SLL can improve companies in achieving sustainability performance targets and supporting the blue economy. This research uses a skinative method with the results showing that SLL provides the potential for lower borrowing costs for borrowers who succeed in sustainability espescily in blue sector . SLL can be one of the funding instruments in the development of a blue economy for the aqua culture sector.